DYNAMICS OF COMMUNITY EMPOWERMENT GROUPS BASED ON TOURISM DEVELOPMENT (CASE STUDY: STEINKOLLEN TOURISM AWARENESS GROUP IN TELUK BAYUR OLD TOWN, BERAU REGENCY): DINAMIKA KELOMPOK PEMBERDAYAAN MASYARAKAT BERBASIS PENGEMBANGAN WISATA (STUDI KASUS: KELOMPOK SADAR WISATA STEINKOLLEN DI KOTA TUA TELUK BAYUR KABUPATEN BERAU) - Muhamad Alisalman; Mustangin; Ihlas Nur Fahman; Faathihsia Ridda Aulya Kur’aeni (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Pokdarwis Steinkollen is one of the organizations that is actively involved in community empowerment based on the development of tourism in the old town of Teluk Bayur. Pokdarwis Stenkollen has been active since 2021 under the name Pokdarwis Kalibata. The development of Pokdarwis is followed by group dynamics and problems which resulted in the name change to Pokdarwis Stenkollen. The purpose of this study was to analyze the dynamics of community empowerment groups based on tourism development through aspects of group communication, conflict within the group, group cohesion, strength and problem solving in the group. The research method used a qualitative case study type. The results of the study showed that, 1. Group communication, there is open communication by holding discussions and meetings. 2. Conflict within the group due to differences in concepts and technicalities in implementing community empowerment programs and political views. 3. Group cohesion is that the administrators and members of the group have a fairly strong emotional relationship, namely the same customs, habits and vision and mission. 4. Strength and problem solving in the group with strong legality and potential for tourism development.